Нужно 40 1) выражение (x-8)(x+8)+64. 2) выражение (2a-5b)(2a+5b) - (6b-3a)(6b+3a). 3) выражение (a-2)(a+2) +4. 4)выполните умножение (x-3y)(x+3y). 5)выполните умножение (m -3n)(m+3n). 6)разложите на множители 49 - 9x^2. 7)решите уравнение (6x-1)(6x+1)-4x(9x+3)=-4. 8)разложите на множители 81-4y^2 9) выражение (3x-4y)(3x+4y) -(6x-2y)(6x+2y). 10)решите уравнение 2x(8x-4) -(4x-2)(4x+2)=-12.
2)(2a-5b)(2a+5b) - (6b-3a)(6b+3a)=4a²-25b²-(36b²-9a²)=
=4a²-25b²-36b²+9a²=13a²-61b²
3) (a-2)(a+2) +4=a²-4+4=a².
4)(x-3y)(x+3y)=x²-9y².
5)(m -3n)(m+3n)=m²-9n².
6)49 - 9x²=(7-3x)(7+3x).
7) (6x-1)(6x+1)-4x(9x+3)=-4.
36x²-1-36x²-12x=-4
-12x=-4+1
-12x=-3
x=(-3):(-12)
x=1/4
8) 81-4y²=(9-2у)(9+2у)
9) (3x-4y)(3x+4y) -(6x-2y)(6x+2y)=(9х²-16у²)-(36х²-4у²)=9х²-16у²-36х²+4у²=
-27х²-12у²
10) 2x(8x-4) -(4x-2)(4x+2)=-12
16х²-8х-(16х²-4)=-12
-8х+4=-12
-8х=-16
х=2
2) = 4a² - 25b² - (36b² - 9a²) = 4а² - 25b² - 36b² + 9a² = 13a² - 61b²
3) = a² - 4 + 4 = a²
4) = x² - 9y²
5) = m² - 9n²
6) = (7 - 3x) (7 + 3x)
7) 36x² - 1 - 36x² - 12x = -4
- 12x = -3
x = 0,25
8) = (9 - 2y) (9 + 2y)
9) = 9x² - 16y² - (36x² - 4y²) = 9x² - 16y² - 36x² +4y² = -32x² -12y²
10) 16x² - 8x - 16x² + 4 = -12
-8x = -16
x = 2